2018
DOI: 10.18632/oncotarget.25558
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of BMI-1 expression by the novel small molecule PTC596 in mantle cell lymphoma

Abstract: Despite the development of the novel Bruton tyrosine kinase inhibitor ibrutinib, mantle cell lymphoma (MCL) remains an incurable B-cell non-Hodgkin lymphoma. BMI-1 is required for the self-renewal and maintenance of MCL-initiating stem cells. Upregulation of BMI-1 has been reported in MCL patients, especially in those with refractory/relapsed disease. We studied the effects of a novel small-molecule selective inhibitor of BMI1 expression, PTC596, in MCL cells. Eight MCL cell lines and patient-derived samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
(57 reference statements)
3
23
0
Order By: Relevance
“…MCL1, an anti-apoptotic protein, is essential for MM cell survival and related to relapse and poor prognosis 36 . In the present study, PTC596 decreased MCL1 levels in MM cells, as reported previously in acute myeloid leukemia and mantle cell lymphoma 13 , 14 . Bortezomib treatment compromises the anti-apoptotic function of MCL1 by promoting its proteolytic cleavage 37 , 38 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MCL1, an anti-apoptotic protein, is essential for MM cell survival and related to relapse and poor prognosis 36 . In the present study, PTC596 decreased MCL1 levels in MM cells, as reported previously in acute myeloid leukemia and mantle cell lymphoma 13 , 14 . Bortezomib treatment compromises the anti-apoptotic function of MCL1 by promoting its proteolytic cleavage 37 , 38 .…”
Section: Discussionsupporting
confidence: 92%
“…Recently, PTC596 has been recognized as a direct microtubule polymerization inhibitor in a preclinical study of pancreatic ductal adenocarcinoma 11 . PTC596 induces cytotoxicity with EC 50 values of 30–200 nM in various tumor cell lines 12 and has preclinical effects on hematological malignancies such as acute myeloid leukemia and mantle cell leukemia 13 , 14 . Clinical trials of PTC596 are ongoing for glioma, leiomyosarcoma, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PTC596 was recently identified as a direct microtubule polymerization inhibitor in a preclinical study on pancreatic ductal adenocarcinoma and its function as a BMI1 modulator was shown to be a secondary effect 4 . PTC596 induces cytotoxicity in various tumor cell lines and exerts preclinical effects on hematological malignancies, such as AML, mantle cell leukemia, and multiple myeloma 5‐7 . Clinical trials on PTC596 are ongoing for diffuse intrinsic pontine glioma, leiomyosarcoma, and ovarian cancer (ClinicalTrials.gov identifiers: NCT03605550, NCT03761095, and NCT03206645).…”
Section: Introductionmentioning
confidence: 99%
“…The protein is often expressed in stem cells, and several reports have implicated its overexpression in cancer stem cell maintenance and the progression of different types of cancers [6][7][8]. By contrast, regulation of BMI1 with inhibitors or short hairpin RNAs (shRNAs) results in cellular senescence or apoptosis of several types of cancer cells [9][10][11][12][13] and sensitizes tumor cells to cytotoxic agents or radiation [14,15]. Because of this, BMI1 is an attractive target for future clinical therapies of different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…BMI1 overexpression is a well-established inducer of cancer cell proliferation and resistance to cancer drug treatments of various cancer cell lines [16][17][18], highlighting the potential of specific BMI1 inhibitors. However, although BMI1 inhibition results in growth reduction and cell death of different cancer cell lines, the underlying mechanisms are often context-dependent and uncertain [11,13,19]. As a result, little is known about the genetic interactions and variations involved in BMI1 inhibition-derived lethality or the subsequent resistance.…”
Section: Introductionmentioning
confidence: 99%